Hybrid nano self-repairing agent, preparation method, antifriction lubricating grease and application

By using core-shell structure nano-self-repairing agent prepared by using composite nanometal particles and nano-inorganic modified coatings in the grease, the problem of agglomeration of nano-self-repair materials in the grease is solved, the stable dispersion and efficient self-repairing effect of the grease are achieved, and the performance and reliability of industrial machinery and equipment are improved.

CN119703050APending Publication Date: 2025-03-28JINLING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411909830.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing nano-self-healing materials are prone to agglomeration in grease, resulting in unstable grease performance and affecting the reliability of friction equipment.

Method used

The composite nanometal particle CoCuAg is used as the core and wrapped with SiO2/Al2O3 nano-inorganic modified coating, an organic/inorganic hybrid nano-self-study agent with a core-shell structure is prepared, and the stable dispersion in the grease is ensured through ultrasonic dispersion and graft polymerization technology.

Benefits of technology

The stable dispersion of nano self-repairing agents in the grease is achieved, the self-repair and anti-wear properties of the grease are improved, and the operation speed, accuracy and production efficiency of industrial machinery friction equipment is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119703050A_ABST
    Figure CN119703050A_ABST
Patent Text Reader

Abstract

The invention discloses a hybrid nano self-repairing agent and a preparation method thereof, anti-friction lubricating grease and application, and belongs to the field of mechanical lubrication.The preparation method of the hybrid nano self-repairing agent comprises the steps that firstly, composite nano metal particles CoCuAg are synthesized; 2, the surface of CoCuAg is coated with a SiO2 / Al2O3 nano inorganic modified coating, and a CM composite material of a core-shell layer structure is obtained; 3, placing the CM composite material in a mixed solvent of deionized water and absolute ethyl alcohol, and adding polyvinyl alcohol to obtain a surface modified CM solution; ethyl cellulose, sodium dodecyl benzene sulfonate and polyvinylpyrrolidone are added into the surface modified CM solution, and a prepolymer CM solution is obtained; heating the prepolymer CM solution, adding methyl acrylate, methyl methacrylate, benzoyl peroxide and divinyl benzene, and reacting to obtain the organic / inorganic hybrid PCM nano self-repairing agent. The invention provides lubricating grease specially designed for industrial mechanical friction equipment. The lubricating grease has excellent wear resistance and excellent self-repairing capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of mechanical lubrication and relates to a friction-reducing grease, in particular to a hybrid nano self-repairing agent and a preparation method, friction-reducing grease and application. Background Art

[0002] During the operation of industrial machinery, friction components will produce friction and loss, which will affect the normal operation and accuracy of the equipment. In order to reduce the cost of equipment maintenance, greases that integrate nano self-repairing elements and have wear resistance and drag reduction functions are currently being developed, showing great market potential. Nanomaterials can penetrate into tiny flaws or cracks in materials due to their tiny size and high surface energy. The filling effect of this nanomaterial can repair the worn area, thereby extending the service life of the material. However, it is worth noting that there are electrostatic forces and van der Waals forces between the particles of nano self-repairing materials, which makes them easy to agglomerate in grease. Therefore, the development of nano self-repairing agents is regarded as the key to grease technology. If the performance of nanomaterials and grease does not match, the performance of the grease will become unstable, which will affect its self-repairing performance and reduce the reliability of friction equipment. Therefore, the development of a new type of nano self-repairing grease with stable dispersibility is crucial to extending the service life of industrial friction equipment and reducing maintenance costs. Summary of the invention

[0003] In view of the problems in the prior art, the present invention provides a hybrid nano self-repairing agent and a preparation method, a friction-reducing grease, and an application. The grease is suitable for use in metal friction equipment, and the low-friction environment it produces helps to improve the operating speed and accuracy of the equipment, thereby improving production efficiency and economic benefits.

[0004] To achieve the above object, the present invention adopts the following technical solutions:

[0005] In a first aspect, the present invention provides a method for preparing a hybrid nano self-repairing agent for anti-friction grease, comprising the following steps:

[0006] Step 1, synthesizing composite nano-metal particles CoCuAg;

[0007] Step 2: Coating SiO on the surface of CoCuAg with chemical plating technology 2 / Al 2 O 3 Nano-inorganic modified coatings are used to obtain CM composite materials with a core-shell structure;

[0008] Step 3: placing the CM composite material in a mixed solvent of deionized water and anhydrous ethanol, adding polyvinyl alcohol to obtain a surface-modified CM solution;

[0009] Adding ethyl cellulose, sodium dodecylbenzene sulfonate and polyvinyl pyrrolidone to the surface modified CM solution, and dispersing by ultrasonic to obtain a prepolymer CM solution;

[0010] The prepolymer CM solution is heated while stirring, and methyl acrylate, methyl methacrylate, benzoyl peroxide and divinylbenzene are added. After the reaction, the solution is washed, centrifuged and dried to obtain an organic / inorganic hybrid PCM nano self-healing agent, the surface of which is grafted with an organic material of polymethyl methacrylate-methyl acrylate (P(MMA-MA)).

[0011] Furthermore, in step one, the synthesis method of CoCuAg is: placing copper sulfate pentahydrate, cobalt sulfate and silver nitrate in deionized water, adding polyvinyl pyrrolidone while stirring, adding benzotriazole dissolved in anhydrous ethanol, adjusting the pH to alkaline, heating to 30-60°C, preferably 50°C, slowly dripping a mixed aqueous solution of hydrazine hydrate and sodium borohydride, reacting for 0.5-2h, preferably 1h, to obtain the CoCuAg; the mass ratio of copper sulfate pentahydrate, cobalt sulfate, silver nitrate, polyvinyl pyrrolidone, benzotriazole, hydrazine hydrate and sodium borohydride is 50:1-10:1-10:1-5:0.5-2:1.5-35:10, preferably 50:5:2:2:1:30:10.

[0012] Specifically, the liquid phase method is used to prepare composite nano-metal particles: hydrazine hydrate and sodium borohydride are used as reducing agents, benzotriazole dissolved in anhydrous ethanol is used as an antioxidant, polyvinyl pyrrolidone is used as a dispersant, and the reaction pH is controlled to be alkaline by changing the different ratios of three metal ion oxidants, namely copper sulfate, cobalt sulfate and silver nitrate. The product is washed with water three times and centrifuged, then washed with ethanol three times and vacuum dried to synthesize CoCuAg composite nano-metal particles.

[0013] Furthermore, in step 2, the synthesis method of the CM composite material is: dispersing the CoCuAg in deionized water, slowly adding Al 2 O 3 and polyethylene glycol, ultrasonic; add ethanol and adjust the pH to acidic; slowly drop ethyl orthosilicate and sodium dodecyl sulfate, heat at 50-70°C for 2-5h, preferably at 60°C for 3h under stirring after hydrolysis to obtain wet gel; dry at 80-120°C for 12-48h, preferably at 100°C for 36h; grind; calcine at 300-500°C for 0.5-2h, preferably at 450°C for 1h to obtain the CM composite material; CoCuAg, Al 2 O 3The usage ratio of polyethylene glycol, ethanol, tetraethyl orthosilicate and sodium dodecyl sulfate is 1-30g: 0.5-3g: 0.05-5g: 10-50mL: 3-20g: 0.05-2g, preferably 20g: 1g: 2g: 30mL: 16g: 0.8g.

[0014] Furthermore, in step 3, during the preparation of the surface-modified CM solution, the amount ratio of the CM composite material, deionized water, anhydrous ethanol and polyvinyl alcohol is 1-50 g: 40-300 mL: 40-300 mL: 1-4 g, preferably 20 g: 200 mL: 200 mL: 2 g; after adding the polyvinyl alcohol, stir, and then ultrasonicate for 10-60 min, preferably 20-30 min;

[0015] During the preparation of the prepolymer CM solution, the mass ratio of the CM composite material, ethyl cellulose, sodium dodecylbenzene sulfonate and polyvinyl pyrrolidone is 1-50: 0.2-0.8: 0.5-3: 0.2-0.8 (preferably 20: 0.5: 1: 0.5;

[0016] During the preparation of the organic / inorganic hybrid PCM nano self-healing agent, the heating temperature of the prepolymer CM solution is 20-70° C., preferably 60° C.; the mass ratio of the CM composite material, methyl acrylate, methyl methacrylate, benzoyl peroxide, and divinylbenzene is 1-50:5-20:1-20:0.005-0.08:0.01-0.6, preferably 20:10:10:0.05:0.5; the reaction is carried out under an inert atmosphere, and the reaction time is 0.5-2h, preferably 1h.

[0017] In a second aspect, the present invention provides a hybrid nano self-repairing agent prepared by the above-mentioned preparation method.

[0018] In a third aspect, the present invention provides a friction-reducing grease comprising the above-mentioned hybrid nano self-repairing agent.

[0019] In a fourth aspect, the present invention provides a method for preparing the above-mentioned anti-friction grease: heating dodecyl hydroxystearic acid, oleic acid, lithium hydroxide, deionized water and industrial gear oil together for a saponification reaction; heating the reaction product to remove moisture therein; adding serpentine powder, the hybrid nano self-repairing agent and industrial gear oil in the puffing stage, stirring and then rapidly cooling to obtain the anti-friction grease.

[0020] Furthermore, during the saponification reaction, the mass ratio of dodecyl hydroxystearic acid, oleic acid, lithium hydroxide, deionized water and industrial gear oil is 200-500: 5-20: 50-200: 300-500: 500-1200, preferably 400: 10: 100: 400: 900; the industrial gear oil is 220N-500N, preferably 500N; the heating temperature is 100-130°C, preferably 130°C, and the time is 1-3h, preferably 2h; the heating temperature for dehydration is 140-160°C, preferably 150°C, and the time is 1-4h, preferably 3h.

[0021] Furthermore, in the expansion stage, the mass ratio of serpentine powder, hybrid nano self-repairing agent and industrial gear oil is 3-10:5-20:1500-2500, preferably 5:5-12:1900; the particle size of serpentine powder is 150-250nm, preferably 200nm; the industrial gear oil is 220N-500N, preferably 500N.

[0022] In a fifth aspect, the present invention provides the use of the above-mentioned anti-friction grease in reducing friction in friction equipment.

[0023] The beneficial effects of the present invention are as follows: the present invention selects nano-metal materials as core-wrapped organic materials to prepare organic / inorganic hybrid nano self-repairing agents with stable dispersion and core-shell structure. When used in grease, it has good self-repairing and anti-wear properties, can produce excellent drag reduction and self-repairing effects on the friction pair surface, and is mainly used in friction equipment in industrial machinery.

[0024] Specifically, CoCuAg alloy is used as the core, which is a metal alloy composition similar to that of metal friction pair materials. 2 / Al 2 O 3 Nano-inorganic modification into an outer shell can greatly improve the wear resistance of grease. The composite powder of self-healing agent grafted with P (MMA-MA) polymer, the extension of polymer chain segments helps the nano-scale core-shell structure self-healing agent to be firmly adsorbed on the friction surface, enhancing the realization of the self-healing function. In grease, ultrafine serpentine has high specific surface area, layered structure, etc. These characteristics make it excellent in lubrication. The combination of this organic / inorganic hybrid spherical nano self-healing agent and layered serpentine shows a significant tribological synergistic effect, reducing the friction coefficient through sliding between points and layers, and playing a lubricating role.

[0025] The lubricating grease of the present invention is a lubricating grease specially designed for industrial mechanical friction equipment, which not only has excellent anti-wear performance, but also has excellent self-repairing ability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1is a TEM image of the CM composite material prepared in Example 1;

[0027] Figure 2 is a TEM image of the organic / inorganic hybrid PCM nano self-healing agent of Example 1;

[0028] Figure 3 This is a wear spot image of the friction pair surface in the wear resistance test of the anti-friction grease in Example 4;

[0029] Figure 4 This is a 5000-fold SEM image of the friction pair surface in the wear resistance test of the anti-friction grease in Example 4;

[0030] Figure 5 This is a wear spot image of the friction pair surface in the wear resistance test of the base grease in Example 1;

[0031] Figure 6 This is a 5000-fold SEM image of the friction pair surface in the wear resistance test of the base grease in Example 1. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific embodiments.

[0033] Example 1

[0034] This embodiment provides a hybrid nano self-repairing agent for anti-friction grease, and the preparation method thereof comprises the following steps:

[0035] Step 1: Preparation of composite nano-metal particles CoCuAg:

[0036] Composite nano-metal particles were prepared by a liquid phase method. 50 g of copper sulfate pentahydrate, 5 g of cobalt sulfate and 2 g of silver nitrate were weighed, added to 600 mL of deionized water, placed in a magnetic stirrer, 2 g of polyvinyl pyrrolidone was added while stirring, 1 g of benzotriazole dissolved in 50 mL of anhydrous ethanol was added, the pH was adjusted to 10 with sodium hydroxide and ammonia water to form a mixed alkaline oxidizing liquid, heated to 50°C, 60 g of 50% hydrazine hydrate and 10 g of sodium borohydride as reducing agents were slowly dripped into the mixed oxidizing liquid, and after reacting for 1 hour, the product was washed with water three times and centrifuged, then washed with ethanol three times and dried in vacuo at 60°C to obtain composite nano-metal particles CoCuAg.

[0037] Step 2: Preparation of CM composite material:

[0038] Disperse 20g CoCuAg in 100mL deionized water, place in a magnetic stirrer, and add 1g Al 2 O 3and 2g polyethylene glycol, ultrasonically treated for 30min, added 30mL ethanol, added HCl to adjust the pH to 4, added 16g ethyl orthosilicate and 0.8g sodium dodecyl sulfate dropwise, and heated at 60°C for 3h after hydrolysis to obtain a wet gel. Next, the wet gel was placed in an oven at 100°C for 36h to dry the moisture to obtain a dry gel. Finally, the dry gel was ground into fine powder and placed in a muffle furnace and heated at 450°C for 1h to obtain a CM composite material. The TEM of the CM composite material is as follows Figure 1 shown.

[0039] Step 3: Preparation of organic / inorganic hybrid PCM nano self-healing agent:

[0040] (i) Place 20 g of CM composite material in a mixed solvent of 200 mL of deionized water and 200 mL of anhydrous ethanol, add 2 g of polyvinyl alcohol and stir, and then disperse it in an ultrasonic cleaner at 600 W for 20 min to prepare a surface-modified CM solution.

[0041] (ii) 0.5 g of ethyl cellulose, 1 g of sodium dodecylbenzene sulfonate and 0.5 g of polyvinyl pyrrolidone were added to the surface modified CM solution, and a prepolymer CM solution was prepared by ultrasonic dispersion.

[0042] (III) The prepolymer CM solution was placed in a constant temperature magnetic stirrer and stirred for 30 minutes, heated to 60°C, and 10g of methyl acrylate, 10g of methyl methacrylate, 50mg of benzoyl peroxide, and 500mg of divinylbenzene were added. The mixed solution was protected by nitrogen for 1 hour, washed and centrifuged, and then placed in a vacuum oven for drying to obtain an organic / inorganic hybrid PCM nano self-healing agent, whose surface grafted organic material is polymethyl methacrylate-methyl acrylate (P(MMA-MA)). The TEM of the organic / inorganic hybrid PCM nano self-healing agent is as follows: Figure 2 As shown, from Figure 2 It can be seen that the surface of the PCM nano self-healing agent is evenly coated with organic matter and has good dispersibility.

[0043] Example 2

[0044] This embodiment provides a friction-reducing grease, and the preparation method thereof is as follows:

[0045] 400g of dodecyl hydroxystearic acid, 10g of oleic acid, 100g of lithium hydroxide, 400g of deionized water, and 900g of 500N industrial gear oil were put into a refining kettle together for a heating saponification reaction at 130°C for 2h. Subsequently, the reaction product was heated at 150°C for 3h to remove the water therein. Next, 5g of 200nm serpentine powder, 5g of the hybrid nano self-repairing agent prepared in Example 1, and 1900g of 500N industrial gear oil were added in the puffing stage, stirred evenly, and the mixture was quickly cooled to obtain a friction-reducing grease, which was recorded as grease G-PCM1.

[0046] The wear resistance of the anti-friction grease was tested using a four-ball friction and wear tester. A load of 490N was applied to the friction pair at room temperature and the rotation speed was 2000 rpm for 1 hour. The test results showed that the wear spot diameter was 0.56 mm and the friction coefficient was 0.544.

[0047] Example 3

[0048] This embodiment provides a friction-reducing grease, and the preparation method thereof is as follows:

[0049] 400g of dodecyl hydroxystearic acid, 10g of oleic acid, 100g of lithium hydroxide, 400g of deionized water, and 900g of 500N industrial gear oil were put into a refining kettle together for a heating saponification reaction at 130°C for 2h. Subsequently, the reaction product was heated at 150°C for 3h to remove the water therein. Next, 12g of 200nm serpentine powder, 12g of the hybrid nano self-repairing agent prepared in Example 1, and 1900g of 500N industrial gear oil were added in the puffing stage, stirred evenly, and the mixture was quickly cooled to obtain a friction-reducing grease, which was recorded as grease G-PCM2.

[0050] The wear resistance of the anti-friction grease was tested using a four-ball friction and wear tester. A load of 490N was applied to the friction pair at room temperature and the rotation speed was 2000 rpm for 1 hour. The test results showed that the wear spot diameter was 0.94 mm and the friction coefficient was 0.743.

[0051] Example 4

[0052] This embodiment provides a friction-reducing grease, and the preparation method thereof is as follows:

[0053] 400g of dodecyl hydroxystearic acid, 10g of oleic acid, 100g of lithium hydroxide, 400g of deionized water, and 900g of 500N industrial gear oil were put into a refining kettle together for a heating saponification reaction at 130°C for 2h. Subsequently, the reaction product was heated at 150°C for 3h to remove the moisture therein. Next, 10g of 200nm serpentine powder, 10g of the hybrid nano self-repairing agent prepared in Example 1, and 1900g of 500N industrial gear oil were added in the puffing stage, stirred evenly, and the mixture was quickly cooled to obtain a friction-reducing grease, which was recorded as grease G-PCM3.

[0054] The wear resistance of the anti-friction grease was tested using a four-ball friction and wear tester. A load of 490N was applied to the friction pair at room temperature and the rotation speed was 2000 rpm for 1 hour. The test results showed that the wear spot diameter was 0.24 mm and the friction coefficient was 0.056. The wear spot on the friction pair surface is shown in the figure below. Figure 3 As shown, the SEM image of the friction pair surface magnified 5000 times is as follows Figure 4 shown.

[0055] Comparative Example 1

[0056] This comparative example provides a base grease, and its preparation method is as follows:

[0057] 50g of 400-mesh natural serpentine was placed in a 500mL ball mill, and 100mL of alcohol was added. The ball mill was used in a planetary ball mill for 5 hours to produce a powder with an average particle size of 200nm. 400g of dodecyl hydroxystearic acid, 10g of oleic acid, 100g of lithium hydroxide, 400g of deionized water, and 900g of 500N industrial gear oil were put into a refining kettle together and heated and saponified at 130°C for 2h. Subsequently, the reaction product was heated at 150°C for 3h to remove the moisture. Next, 10g of 200nm serpentine powder and 1900g of 500N industrial gear oil were added in the expansion stage, stirred evenly, and the mixture was quickly cooled to obtain a base grease, which was recorded as grease G-1.

[0058] The wear resistance of the grease was tested using a four-ball friction and wear tester. A load of 450N was applied to the friction pair at room temperature and the rotation speed was 2000 rpm for 1 hour. The test results showed that the wear spot diameter was 1.15 mm and the friction coefficient was 0.921. The wear spot on the friction pair surface is shown in the figure below. Figure 5 As shown, the SEM image of the friction pair surface magnified 5000 times is as follows Figure 6 shown.

[0059] Comparative Example 2

[0060] This comparative example provides a lubricating grease with added CoCuAg nanometal, and the preparation method thereof is as follows:

[0061] 400g of dodecyl hydroxystearic acid, 10g of oleic acid, 100g of lithium hydroxide, 400g of deionized water and 900g of 500N industrial gear oil were put into a refining kettle and heated for saponification at 130°C for 2h. Subsequently, the reaction product was heated at 150°C for 3h to remove the water therein. Next, 5g of 200nm serpentine powder, 5g of the composite nano-metal particles CoCuAg prepared in Example 1 and 1900g of 500N industrial gear oil were added in the puffing stage, stirred evenly and the mixture was quickly cooled to obtain a grease with CoCuAg nano-metal added, which was recorded as grease G-CoCuAg.

[0062] The wear resistance of the grease was tested using a four-ball friction and wear tester. A load of 490N was applied to the friction pair at room temperature and the rotation speed was 2000 rpm for 1 hour. The test results showed that the wear spot diameter was 0.94 mm and the friction coefficient was 0.743.

[0063] Comparative Example 3

[0064] This comparative example provides a grease with a CM composite material added, and the preparation method thereof is as follows:

[0065] 400g of dodecyl hydroxystearic acid, 10g of oleic acid, 100g of lithium hydroxide, 400g of deionized water, and 900g of 500N industrial gear oil were put into a refining kettle and heated for saponification at 130°C for 2h. Subsequently, the reaction product was heated at 150°C for 3h to remove the water therein. Next, 5g of 200nm serpentine powder, 5g of the CM composite material prepared in Example 1, and 1900g of 500N industrial gear oil were added in the expansion stage, stirred evenly, and the mixture was quickly cooled to obtain grease, which was recorded as grease G-CM.

[0066] The wear resistance of the grease was tested using a four-ball friction and wear tester. A load of 490N was applied to the friction pair at room temperature and the rotation speed was 2000 rpm for 1 hour. The test results showed that the wear spot diameter was 0.72 mm and the friction coefficient was 0.589.

[0067] Figure 5 and Figure 6 It shows that when using the base grease, the steel ball friction surface produces deeper wear marks under load conditions; in contrast, Figure 3 and Figure 4The figure below shows the effect of adding PCM self-repairing agent to the grease. The wear marks on the friction surface of the steel ball are obviously lighter under the same load. It can be inferred from these two figures that the grease containing self-repairing agent exhibits better wear resistance and self-repairing ability. Figure 4 It was further revealed that under the action of grease with ultra-fine self-healing agent added, more deposits appeared on the friction pair surface, while the number of voids on the wear surface decreased. This is because the self-healing agent powder actively moved to the friction interface and deposited under the action of external force, constructing a thicker repair layer, which effectively alleviated surface wear.

[0068] In the present invention, unless otherwise specified, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. In addition, the reagents, materials and operating procedures used herein are reagents, materials and conventional procedures widely used in the corresponding fields.

[0069] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a hybrid nano self-repairing agent for anti-friction grease, characterized in that: The following steps are involved: Step 1, synthesizing composite nano-metal particles CoCuAg; Step 2: coating the surface of the CoCuAg with a SiO2 / Al2O3 nano inorganic modified coating to obtain a CM composite material with a core-shell structure; Step 3: placing the CM composite material in a mixed solvent of deionized water and anhydrous ethanol, adding polyvinyl alcohol to obtain a surface-modified CM solution; Adding ethyl cellulose, sodium dodecylbenzene sulfonate and polyvinyl pyrrolidone to the surface modified CM solution to obtain a prepolymer CM solution; The prepolymer CM solution is heated, and methyl acrylate, methyl methacrylate, benzoyl peroxide and divinylbenzene are added to react to obtain an organic / inorganic hybrid PCM nano self-healing agent.

2. The method for preparing the hybrid nano self-repairing agent according to claim 1, characterized in that: In step 1, the synthesis method of the CoCuAg is as follows: copper sulfate pentahydrate, cobalt sulfate and silver nitrate are placed in deionized water, polyvinyl pyrrolidone is added while stirring, benzotriazole dissolved in anhydrous ethanol is added, the pH is adjusted to alkaline, heated to 30-60° C., a mixed aqueous solution of hydrazine hydrate and sodium borohydride is slowly added dropwise, and the reaction is performed for 0.5-2 hours to obtain the CoCuAg; The mass ratio of copper sulfate pentahydrate, cobalt sulfate, silver nitrate, polyvinyl pyrrolidone, benzotriazole, hydrazine hydrate and sodium borohydride is 50:1-10:1-10:1-5:0.5-2:1.5-35:

10.

3. The method for preparing the hybrid nano self-repairing agent according to claim 1, characterized in that: In step 2, the synthesis method of the CM composite material is: dispersing the CoCuAg in deionized water, slowly adding Al2O3 and polyethylene glycol while stirring, and ultrasonicating; adding ethanol and adjusting the pH to acidic; slowly dropping ethyl orthosilicate and sodium dodecyl sulfate, heating at 50-70°C for 2-5h after hydrolysis to obtain a wet gel; After drying and grinding, calcining at 300-500° C. for 0.5-2 h to obtain the CM composite material; The usage ratio of CoCuAg, Al2O3, polyethylene glycol, ethanol, tetraethyl orthosilicate and sodium dodecyl sulfate is 1-30g: 0.5-3g: 0.05-5g: 10-50mL: 3-20g: 0.05-2g.

4. The method for preparing the hybrid nano self-repairing agent according to claim 1, characterized in that: In step 3, the ratio of the CM composite material, deionized water, anhydrous ethanol and polyvinyl alcohol is 1-50 g: 40-300 mL: 40-300 mL: 1-4 g; after adding polyvinyl alcohol, stir, and then ultrasonicate for 10-60 min; The mass ratio of the CM composite material, ethyl cellulose, sodium dodecylbenzene sulfonate and polyvinyl pyrrolidone is 1-50: 0.2-0.8: 0.5-3: 0.2-0.8; The heating temperature of the prepolymer CM solution is 20-70° C. The mass ratio of the CM composite material, methyl acrylate, methyl methacrylate, benzoyl peroxide and divinylbenzene is 1-50:5-20:1-20:0.005-0.08:0.01-0.

6. The reaction is carried out under an inert atmosphere for a reaction time of 0.5-2h.

5. The hybrid nano self-repairing agent obtained by the preparation method according to any one of claims 1 to 4.

6. A friction-reducing grease, characterized in that: Contains the hybrid nano self-repairing agent as claimed in claim 5.

7. The method for preparing the anti-friction grease according to claim 6, characterized in that: Dodecyl hydroxystearic acid, oleic acid, lithium hydroxide, deionized water and industrial gear oil are heated together for saponification reaction; the reaction product is subjected to heat treatment to remove moisture therein; serpentine powder, the hybrid nano self-repairing agent and industrial gear oil are added in the expansion stage, stirred and then rapidly cooled to obtain the anti-friction grease.

8. The method for preparing the anti-friction grease according to claim 7, characterized in that: During the saponification reaction, the mass ratio of dodecyl hydroxystearic acid, oleic acid, lithium hydroxide, deionized water and industrial gear oil is 200-500: 5-20: 50-200: 300-500: 500-1200; the industrial gear oil is 220N-500N; the heating temperature is 100-130°C, and the time is 1-3h; The heating temperature for dehydration is 140-160°C and the time is 1-4 hours.

9. The method for preparing the anti-friction grease according to claim 7, characterized in that: In the expansion stage, the mass ratio of serpentine powder, hybrid nano self-repairing agent and industrial gear oil is 3-10:5-20:1500-2500; the particle size of serpentine powder is 150-250nm; and the industrial gear oil is 220N-500N.

10. Use of the anti-friction grease as claimed in claim 6 in reducing friction in friction equipment.